Determinants of user acceptance and use of open government data (OGD): An empirical investigation in Bangladesh. (February 2019) - Talukder, Md Shamim; Shen, Liang; Hossain Talukder, Md Farid; Bao, Yukun
Abstract: Despite the benefits of transparency, accountability, and participation of open government data (OGD), low acceptance and use of OGD have been observed. However, the acceptance and use of OGD has not been adequately addressed in existing literature. Therefore, this study aimed to synthesize the strengths of two well-established theories; the unified theory of acceptance and use of technology (UTAUT) and IS success model as there is a need to develop a parsimonious model. The research model was empirically validated using 385 responses from a developing Country-Bangladesh. Data were analyzed using partial least square (PLS) technique, a statistical tools based on structured equation modeling (SEM). The results revealed that performance expectancy, effort expectancy, social influence, system quality, and information quality had significant direct and indirect effects on OGD adoption. Theoretically, this research provides a basis for advance enhancement of individual models of technology acceptance. Practically, this research provides several valuable policy guidelines to carry out the better policies and strategies to endorse the acceptance and use of OGD. Highlights: This study addresses the issue of open government data (OGD) adoption and use. UTAUT and IS success model are integrated to end up a comprehensive framework. System quality and Information quality are the key factors.